5-Hydroxymethyl furfural modified melamine glyoxal resin. Issue 13 (2nd October 2020) - Xi, Xuedong; Liao, Jingjing; Pizzi, Antonio; Gerardin, Christine; Amirou, Siham; Delmotte, Luc
ABSTRACT: Glyoxal as a nonvolatile and nontoxic aldehyde, which can be used as a substitution of formaldehyde in wood industry to prepare novel melamine-glyoxal (MG) resins. However, for the reason of the lower reactivity of the glyoxal compared with formaldehyde, the performances of the MG resin is not as good as expected. 5-Hydroxymethyl furfural (HMF) was used as a modifier to improve the properties of melamine-glyoxal (MG) resins to prepare a hydroxymethyl furfural modified melamine-glyoxal (HMFMG) resin. This was tried as a plywood adhesive. Matrix-assisted laser desorption ionization time of flight (MALDI-TOF), Cross Polarisation-Magic Angle Spinning Nuclear Magnetic Resonance (CP-MAS 13 C NMR), Differential Scanning Calorimetry (DSC), and thermomechanical analysis (TMA) were used to analyze the structure of the oligomers formed and the thermomechanical properties of the resins. The curing activation energy of HMFMG resin was found to be lower than MG resin, and it also significantly with a better plywood bonding performance and water resistance.